2022
DOI: 10.1111/ene.15255
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and associated factors of motoric cognitive risk syndrome in multiple ethnic middle‐aged to older adults in west China: a cross‐sectional study

Abstract: Background and purpose: Motoric cognitive risk (MCR) syndrome characterized by subjective cognitive complaints and slow gait has been proposed and validated as a pre-dementia syndrome. The overall and specific ethnic prevalence of MCR and the associated factors are poorly understood in middle-aged to older community-dwelling residents in west China. Methods:The present study included 6091 samples from the prospective cohort study, West China Health and Aging Trend (WCHAT). Multidimensional factors of demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 51 publications
(122 reference statements)
0
27
1
1
Order By: Relevance
“…The present study extended previous studies by providing the prevalence of MCR among community-dwelling older adults in the Central area of China. The prevalence of MCR was 11.5% in the present study (mean age = 71.62 ± 5.22), which was among the reported range of 9.6% ~ 12.7%(9.6% in Beijing, China [ 31 ], 10% worldwide [ 5 ], 12.7% in East China, 10.7% in West China [ 8 ], and 10.4% in a nationally Chinese sample [ 34 ]. Slightly different results might be related to assessment tools, participants of diverse ages, ethics, and senior hospital departments [ 5 , 8 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The present study extended previous studies by providing the prevalence of MCR among community-dwelling older adults in the Central area of China. The prevalence of MCR was 11.5% in the present study (mean age = 71.62 ± 5.22), which was among the reported range of 9.6% ~ 12.7%(9.6% in Beijing, China [ 31 ], 10% worldwide [ 5 ], 12.7% in East China, 10.7% in West China [ 8 ], and 10.4% in a nationally Chinese sample [ 34 ]. Slightly different results might be related to assessment tools, participants of diverse ages, ethics, and senior hospital departments [ 5 , 8 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 52%
“…The prevalence of MCR was 11.5% in the present study (mean age = 71.62 ± 5.22), which was among the reported range of 9.6% ~ 12.7%(9.6% in Beijing, China [ 31 ], 10% worldwide [ 5 ], 12.7% in East China, 10.7% in West China [ 8 ], and 10.4% in a nationally Chinese sample [ 34 ]. Slightly different results might be related to assessment tools, participants of diverse ages, ethics, and senior hospital departments [ 5 , 8 , 31 , 34 ]. Our results found aging awareness, and positive control were associated with MCR risk after adjusting for related confounders.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The operational definition of MCR was the presence of SCCs and SG but without dementia or mobility disability, as proposed and validated by Verghese et al’s (2012 , 2014 ), Maggio and Lauretani (2019) , and Stephan et al (2020) . The diagnosis of present MCR was described elsewhere in detail ( Sun et al, 2022 ). Dementia was identified by self-and/or proxy-reported previous diagnoses by physicians.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we have previously linked overall support and tangible support to gray matter volume, primarily in prefrontal, hippocampal, cingulate, insular, and thalamic brain regions ( Cotton et al, 2019 ), which overlap with brain areas linked to the MCR syndrome ( Blumen et al, 2018 ; 2021 ). A recent study has also shown that increased social support utilization (or support seeking behaviors) is associated with a reduced risk for MCR in middle-aged to older adults ( Sun et al, 2022 ). Based on these studies—highlighting the shared cognitive outcomes and shared neural substrates of MCR and different kinds of social support, along with initial evidence that support seeking behaviors are associated with a reduced risk for MCR—we hypothesized that increased levels of social support would decrease the risk for developing MCR.…”
mentioning
confidence: 99%